2‐Ethylhexanol Derivatives as Nonionic Surfactants: Synthesis and Properties. Issue 1 (30th November 2015) - Hreczuch, Wiesław; Dąbrowska, Karolina; Chruściel, Arkadiusz; Sznajdrowska, Agata; Materna, Katarzyna
Abstract: The synthesis and basic properties of 2‐ethylhexanol based innovative nonionic surfactants are described in this paper. 2‐Ethylhexanol as an available and relatively inexpensive raw material was used as the hydrophobe source modified by propoxylation and followed by polyethoxylation. As the result, six series of 2‐ethylhexyl alcohol polyalkoxylates (EHP m E n ) were obtained with three steps of propoxylation, each followed by polyethoxylation and two series only with polyethoxylation (EHE n ). Two different catalysts were used, a dimetalcyanide and KOH. Values of average conversion rates and chemical content of the obtained products (GC, TG and GPC techniques) were compared. The influence of the applied catalyst and polyaddition degree on the homologue distribution, reactant conversion and amount of byproducts is discussed. The basic physicochemical parameters including refractive index, solubility in polar media, foaming properties and wettability were investigated and compared. Furthermore, surface activity parameters, i.e. surface tension ( γ CMC ) and critical micelle concentrations were determined. Results are compared to C12–14 alcohol ethoxylates (LaE n ). Accordingly, it was found that the studied 2‐ethylhexyl alcohol based compounds are effective, low foaming nonionic surfactants.